"ABK SMILE' Pocketbook as a Dental Media Educational Media for Accompanying Children with Special Needs at SLB Widya Bhakti Semarang - Sandy Christiono; Regilia Shinta Mayangsari; Silvia Vera Indrawati (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract: Children with Special Needs (ABK) need to get more attention related to dental and oral health because ABK has a higher prevalence of problems in the oral cavity than normal children. The oral and dental health of children with special needs depends on their parents or companions because they play the role of the closest person who educates, trains, and gives love to the child. ABK assistants must have the skills and knowledge to teach ABK about the importance of maintaining healthy teeth and mouth, one of which is by giving pocketbooks. Method: The method used uses the Participatory Action Research (PAR) strategy by empowering the community. The pocketbook is given free of charge to the ABK companion and a follow-up is carried out for 3 months. Result: Service activities carried out at SLB Widya Bhakti Semarang for 3 months consisting of preparation, implementation and evaluation stages. There was a change in oral hygiene which was initially categorized as good. This pocket book is effective in providing education because it is interesting and easy to learn for children. Conclusion : This pocketbook "ABK Smile" can help improve education for children with special needs.